Getting by with a little help from my friends: The contribution of mentorship practices to the social learning of the novice lecturer in the capacity of being an academic - Ramhurry, R.; Luneta, K. (South African Journal of Higher Education, 2021)
The challenges novice lecturers experience when integrating into the South African Higher Education (HE) landscape are well documented. This article reports on the novice lecturers’ experiences of mentorship practices in their first year of teaching at a Higher Education (HE) institution in Johannesburg, South Africa. An Interpretivist paradigm was used to gain insight into their experiences of assimilating into academic life. The theories, which offered good purchase on the social learning of novice lecturers and therefore underpin this article, are social constructivism as a scaffold to mentoring theory and communities of practice. Data was generated through discursive oriented interviews and analysed using using Thematic analysis in conjunction with Discourse Analysis. Using a purposeful sampling strategy, the participants in the study were ten novice lecturers, who were drawn from various disciplines. The study found that although novice lecturers’ passage into academia was initially problematic in the sense of being alienating and lonely, they created invisible networks of resourceful relationships which served as ways to survive and ultimately manage their new roles and responsibilities.